The Impact of Technological Change on Immigration and Immigrants - Yvonne Giesing (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the effects of technological change on immigration flows as well as the labor market outcomes of migrants versus natives. We analyse and compare the effects of two different automation technologies: Industrial robots and artificial intelligence. We exploit data provided by the Industrial Federation of Robotics as well as online job vacancy data on Germany, a highly automated economy and the main destination for migrants in Europe. We apply an instrumental variable strategy and identify how robots decrease the wage of migrants across all skill groups, while neither having a significant impact on the native population nor immigration flows. In the case of AI, we determine an increase in the wage gap as well as the unemployment gap of migrant and native populations. This applies to the low-, medium- and high-skilled and is indicative of migrants facing displacement effects, while natives might benefit from productivity and complementarity effects. In addition, AI leads to a significant inflow of immigrants. Policymakers should devote special attention to the migration population when designing mitigation policies in response to technological change to avoid further increases in inequality between migrants and natives.
Keywords: F22; J15; J61; J78; O15; O33; 330; technological change; AI; robots; immigration